Neuropathology of neurodegenerative disorders - Kril, Jillian (Henry Stewart Talks, 2007)
Current neuropathological diagnostic criteria for neurodegenerative disorders, Major macroscopic and microscopic features, Pattern and extent of brain atrophy, Alzheimer's disease, Lewy body diseases, Frontotemporal dementia, Other tauopathies, Huntington's disease, Motor Neurone Disease
Archived at 2021/06/29